The Use of Derivation and Inflection in BCC News's “Tory Gloom Ahead of Triple By-Election Test” - Sari, Fatia Novita; Rudianto, Gaguk (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2024)
The purpose of this research is to examine the process of inflectional affixation and derivation in the BCC news article entitled “Tory Gloom Ahead of Triple By-Election Test." The study also described the affixation occurrences within sentences and words present in the article. To describe and analyze the data, this study used a qualitative research design by Creswell, the method of collecting by note-taking and highlighting the data and analyzing data by summarizing the data based on inflection and derivation proposed by Sudaryanto. To facilitate the identification of derivation and inflectional affixations, the writers employ a table to categorize each affixation process. The focus of this investigation is on English words that undergo derivational and inflectional affixation processes. The data for analysis are derived from a written text; therefore, the documentation method is utilized for this study. The findings reveal a total of 47 affixes present in the analyzed articles, consisting of both derivation and inflectional affixes. Among them, 17 affixes are classified as derivations, while the remaining 29 are inflections. The author concludes that the article "Tory Gloom M About the Triple By-Election Test" contains words that have undergone an affixation process, both derivational and inflectional and it turns out that there are more inflectional than derivational. Hopefully, this research can add insight to readers or can be a reference for readers who want to research morphology or, more precisely, the process of affixation.